Cecum Volvulus, In Misdiagnosis of Acute Appendicitis: a case report - Tahir, Shenol; Ambardjieva, Martina; Jovanovska, Frosina; Mustafova, Alma; Dervisov, Kristijan; Limani, Nimetula; Markov, Petar; Dalipi, Berat (My University, 2021)
Cecum Volvulus, In Misdiagnosis of Acute Appendicitis: a case report Şenol Tahir, Martina Ambardjieva, Frosina Jovanovska, Alma Mustafova, Kristijan Dervisov, Nimetula Limani, Petar Markov, Berat Dalipi University Clinic for Surgical Diseases, General and Abdominal Departemen – St.Naum Ohridski, Skopje, N. Macedonia Background: As a type of intestinal malrotation, colon volvulus is most common in the sigmoid, followed by the caecum and then the transverse and splenic flexure. The cause of volvulus may be due to embryologically incomplete rotation of the intestine, Ledd’s bands, long mesocolon, or dolichocolon. Methods/Results: Preoperative diagnosis of cecal volvulus is usually accidental and can be confirmed by CT of the abdomen, and it is an incidental intraoperative finding in most cases. We present a patient with an operative diagnosis for acute appendicitis, with Alvarado score of 8 and positive ultrasonographic signs for acute appendicitis. On laparoscopic exploration for appendectomy, an enormously dilated colon (bigger cystic formation) affects the entire pelvis. The conversion was performed with lower median laparotomy, cecal volvulus found with 360-degree rotation in the direction of the clock’s hands with more significant deterioration of the caecum. Right hemicolectomy was performed with ileum- transverse colon double GIA stapler anastomosis. On the 6th postoperative day, the patient was discharged home. Conclusions: Cecal volvulus although a rare acute surgical condition should be recognized and properly surgically treated.
Keywords: cecal volvulus; acute appendicitis